STUNTING COUNTERMEASURES THROUGH THE GEMA BERCETING APPLICATION - Probowati, Ririn; Arief, Yuni Sufyanti; Mubarrok, Alik Septian (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: In the National Medium-Term Development Plan (RPJMN) 2020-2024 and Presidential Regulation No. 72 of 2021 targets reducing stunting to 14 percent by 2024, improving the quality of family life preparation, ensuring the fulfillment of nutritional intake, and improvingparenting. This study aimed to prevent and reduce stunting by involving the Family Assistance Team (TPK) movement.Method: The design in this study is pre-experimental analytics with one group pre-test and post-test design. This study analyzes the development of knowledge, skills, and motivation of TPK in assisting and fostering the community to reduce and prevent stunting based on the GEMA BERCETING Application (Movement for The Eradicated and Prevent stunting Community). Results: The results showed that there were differences in knowledge, skills, and motivation of TPK due to the application of the GEMA BERCETING Application with the results of the independent t-test obtained a t value of 9.09 (p = 0.008).Results: The results showed that there were differences in knowledge, skills, and motivation of TPK due to the application of the GEMA BERCETING Application with the results of the independent t-test obtained at the value of 9.09 (p = 0.008).Conclusion: The conclusion of this study is the application of the GEMA BERCETING JombangApplication is structured to contain the features and designs needed to provide education related to stunting prevention and reduction to facilitate TPK in Peterongan District, which can easily use this application. to provide services to the community in overcoming and preventing stunting.